Antibacterial Efficacy of Surface Modified Gutta Percha with Zinc Oxide Nanoparticle - G, Manobharathi; Raghu, Sandhya (Journal of Neonatal Surgery, 2025)
Background: Endodontic treatment may fail due to secondary or persistent infection. Failure of endodontic treatment may arise from the microorganisms that survived root canal therapy and those in root canal filling materials. Aim: The aim of this study was to increase the antimicrobial efficacy of commercial Gutta percha cones by modifying the surface with thin deposition of zinc oxide nanoparticles. Materials and methods: Zinc oxide nanoparticles were synthesized using a chemical precipitation method and incorporated into a polyvinyl acetate (PVA) polymer solution for surface coating. Commercial gutta-percha cones were sterilized and divided into two groups: uncoated (control) and ZnO nanoparticle–coated. The antibacterial activity against Enterococcus faecalis was evaluated using a direct contact test, and bacterial growth was assessed by colony-forming unit (CFU) counts. Result: Zinc oxide nanoparticle–coated gutta-percha cones demonstrated markedly greater antimicrobial efficacy than uncoated cones, showing nearly a ten-fold reduction in Enterococcus faecalis colony counts. Conclusion: Within the limitations of this in vitro study, zinc oxide nanoparticle coating significantly enhanced the antimicrobial activity of gutta-percha cones against Enterococcus faecalis, suggesting its potential as an effective modification to reduce bacterial persistence in root canal therapy.